Territorial Changes and International Conflict - Goertz, Gary; Diehl, Paul (New York : Routledge Florence : Taylor & Francis Group [distributor], 1992)
Annotation This book charts the incidence of territorial changes and military conflicts from 1816 to 1980. Using statistical and descriptive analysis, the authors attempt to answer three related sets of questions: * When does military conflict accompany the process of national independence? * When do states fight over territorial changes and when are such transactions completed peacefully? * How do territorial changes affect future military conflict between the states involved in the exchange?
Trade
Keywords: Territory, National; International Relations; Political Science -- General; Law -- International; Political Science -- International Relations -- General